Kepastian Hukum Aset Digital sebagai Objek Jaminan dalam Perjanjian Kredit - Alfia Salsabila; Rachmadi Usman (YASIN, 2026)
Although digital assets have received attention in various previous studies, studies that specifically discuss legal certainty and the enforcement framework for digital asset collateral under Indonesian civil security law remain limited. This study aims to analyze the concept of digital assets as “objects” in Indonesian property law in relation to ownership rights and to identify normative obstacles and mechanisms for enforcing digital asset collateral in the event of debtor default. This study uses a qualitative approach with a doctrinal design through normative legal research based on statutory and conceptual approaches. The data used were secondary data, including primary, secondary, and tertiary legal materials, and were then analyzed using qualitative descriptive-analytical analysis. The results show that digital assets legally meet the requirements as intangible movable objects under Article 499 and Article 503 of the Indonesian Civil Code because they can be controlled through a private key, have economic value, and form part of a person’s assets. However, the enforcement of digital asset collateral still faces fundamental obstacles due to the decentralized characteristics of blockchain, the technical principle of “not your keys, not your coins,” extreme volatility, and the normative vacuum in the Fiduciary Security Law. The conclusion of this study affirms that the use of accredited custodial institutions can serve as a point of legal intervention to secure the enforcement mechanism for digital asset collateral. The implications of this study include theoretical contributions to the development of principles of immaterial property law and a practical framework for the Financial Services Authority (OJK) in formulating cross-sectoral regulations on digital assets as collateral objects.